Long-term decline of regions and the rise of populism: The case of Germany - Maria Greve; Michael Fritsch; Michael Wyrwich (Journal of Regional Science, 2022)
What characterizes regions where right-wing populist parties are relatively successful? A prominent hypothesis proposed in the emerging “geography of discontent” literature claims that places that are “left behind” constitute a breeding ground for the rise of populism. We re-examine this hypothesis by analyzing the rise of populism in Germany. Our results suggest that high vote shares of populist parties are associated with the long-term decline of a region's relative welfare, which goes beyond a lifespan of people inhabiting such “left behind” places. Moreover, we are able to show that a place-based collective memory about past prosperity plays a crucial role in shaping present resentment. Finally, we find the education level of the regional population to be an important channel through which the collective memory about the past translates into populism support today.
Keywords: 320; economic development; economic history; populism; territorial inequality